Growth modulation of nonlayered 2D-MnTe and MnTe/WS2 heterojunctions for high-performance photodetectors. Issue 4 (10th January 2023) - Wang, Taikun; Sun, Fapeng; Hong, Wenting; Jian, Chuanyong; Ju, Qinkun; He, Xu; Cai, Qian; Liu, Wei
Abstract : A comparison between the photoelectric performance of a two-dimensional MnTe-based photodetector and a two-dimensional MnTe–WS2 -based photodetector. Abstract : Two-dimensional materials and heterojunctions have shown great potential in miniaturized high-performance photodetectors. MnTe, as a nonlayered p-type semiconductor, possesses excellent optoelectronic properties. However, a method to grow 2D MnTe with a few nanometers of thickness is still lacking. In this paper, we report the growth of ultrathin MnTe nanosheets on mica by the chemical vapor deposition (CVD) method. By tuning the growth conditions, the thickness of the nanosheets can be controlled from 1.36 nm to 100 nm by tuning the gas flow rate. The H2 concentration in the carrier gas can control the shape of the MnTe nanosheets. In addition, MnTe/WS2 heterojunctions fabricated by the mechanical stacking method exhibited excellent photoresponsivity (0.271 A W −1 ), external quantum efficiency (EQE, 527%), and photodetectivity (1.23 × 10 10 Jones) at an illumination of 637 nm @ 0.151 mW cm −2 at 3 V, as well as higher photoresponse speed (compared with the MnTe-based photodetector). This work provides a possible application of MnTe-based heterojunctions for developing high-performance photodetectors.